DIGITALISASI PEMBELAJARAN SEJARAH SD MELALUI TUR VIRTUAL GOOGLE ARTS & CULTURE PADA MATERI CANDI MASA KLASIK HINDU-BUDDHA - Ilham Arya Susanto; Budiansyah; Najlatul Fathia; Dwi Septiyanda; Fanny Zakkiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of using Google Arts & Culture virtual tours on elementary school students’ understanding of Hindu-Buddhist classical temple materials. The study employed a quantitative approach using a pre-experimental design through a one-group pretest-posttest design model. The research was conducted at SD Negeri 28 Palembang City with 28 fourth-grade students as the research subjects. Data collection techniques included tests, observations, and documentation. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, paired sample t-test, and N-Gain test. The results showed that the students’ average score increased from 61.25 in the pretest to 86.43 in the posttest, with an improvement of 25.18 points. The percentage of students achieving learning mastery increased from 32.14% to 89.29%. The paired sample t-test result showed a significance value of 0.000 < 0.05, indicating that the use of Google Arts & Culture virtual tours had a significant effect on students’ understanding. In addition, the N-Gain test result of 0.65 indicated a moderate improvement category. Learning through virtual tours helped students understand temple structures, reliefs, and the life of Hindu-Buddhist societies in a more concrete and interactive manner. Therefore, Google Arts & Culture virtual tours can serve as an innovative, economical, and relevant alternative medium for history learning in accordance with the needs of 21st-century education.